Perfil competitivo de las empresas del subsector de la impresión en serigrafía e ID gran formato en la Comunidad de Madrid: Análisis basado en la tipología de estrategias de Miles y Snow (1978) - Rubén Esteban Bermejo; Enrique Nieto Carrami\~nana; Julio García del Junco (Atlantic Review of Economics, 2013)
– Miles & Snow's typology, along with Porter's, are the most popular and contrasted ones. They have been used in multiple researches for the characterization of the competitive and strategic behaviour of companies in different sectors. In this study we aim to describe the competitive profile according to the generic strategy of Miles and Snow (1978) in the companies of serigraphic impression and digital impression in big size in the Madrid region. In that aim we conducted an empirical study with a sample of 136 companies of the mentioned sector in the Madrid Region. In the descriptive analysis, based in the medium values provided by the executives of the companies to the different questions, we will find enough information to obtain the prevailing competitive profile (prospector, defender and reactor). At the same time, a series of minor goals and recommendations have been established. The minor goals consisted in determining the relation between the size, the age and years of career of executives with the competitive profiles of Miles and Snow (1978). The results obtained show that the companies orient themselves towards an analyzing profile, that invests on machinery, but due to the crisis and the permanent evolution of the sector, analyzes in detail the risks.
Keywords: 330; Miles y Snow; Strategic; Serigraphic and Digital Impression; Innovation; Crisis